Role of Nitric Oxide in the Modulation of Angiogenesis - Morbidelli, L.; Donnini, S.; Ziche, M. (Current Pharmaceutical Design, 2003)
Angiogenesis, the development of new capillaries form pre-existing vessels, requires the coordinate activation of endothelial cells, which migrate and proliferate in response to growth factors to form functional vessels. Therapeutic angiogenesis is proposed to restore tissue integrity and function following damage and ischemia, while strategies aimed to block or suppress the neovascular growth are designed as adjuvant therapies for cancer treatment. Different experimental and clinical observations support the existence of a molecular / biochemical link between vasodilation, nitric oxide (NO) production and angiogenesis. NO significantly contributes to the prosurvival / proangiogenic program of capillary endothelium by triggering cell growth and differentiation via endothelial-constitutive NO synthase (ecNOS) activation, and cyclic GMP (cGMP) dependent gene transcription. Re-establishment of a balanced NO production in the cardiovascular system results in a reduction of cell damage during inflammatory and vascular diseases. Elevation of NOS activity in correlation with angiogenesis and tumor growth and aggressiveness has been extensively reported in experimental and human tumors. On these bases, the nitric oxide pathway appears to be a promising target for the development of pro- and anti-angiogenic therapeutic strategies. In particular, the use of NOS inhibitors or NO scavengers seems appropriate to reduce edema, block angiogenesis and facilitate antitumor drug delivery.
Keywords: nitric oxide